Instrument control system – the communication between DigitalMicrograph and Keithley instrument for in situ TEM application - Nguyen, Hong Hai (2018)
Transmission electron microscopy (TEM) is an atomic resolution microscopic technique that has numerous applications in medical research, material sciences, and life science. Recently, the need to observe samples under TEM in real time has resulted in a so-called in situ and operando TEM experiment. However, there are many problems concerning this technique, one of them is a problematic synchronization of quantitative measurement and image acquisition when using multi-computer to operate TEM and to control the external stimuli. In this report, a development process and detailed explanation of an instrument control system are reported. This control system, including a C++ plugin and a DM script, will allow one to control simultaneously the TEM to acquire images and the Keithley source meter unit to apply electrical biases via single window DigitalMicrograph (DM) application and thus can solve thereof problem. A CVD graphene on a cryo-TEM chip was characterized under TEM to test the capability of the control system. Through the application of various electrical bias conditions, the current – voltage characteristics of the graphene were obtained, suggesting appropriate functionality of the system. The breakdown point of the graphene under a large electrical field was recorded, in which the TEM images and the electrical information were simultaneously acquired. As a result, one can achieve better understandings of mechanisms by observing how materials behave under different external stimuli down to atomic-scaled resolution. Successful implementation of the instrument control system has solved the synchronizing problem and enable the automatization of the image and data acquisition.